Preimplantation aneuploidy screening using embryonic cell-free DNA isolated from spent culture medium: a case report - Lama Khudari; Marwan Halabi; Sahar Al Fahoum (Egyptian Journal of Medical Human Genetics)
Abstract Background Chromosomal aberrations are frequent in human embryos and can be identified during IVF by performing preimplantation genetic testing for aneuploidies (PGT-A). Therefore, this study presents a case report highlighting the application of embryonic cell-free DNA isolated from spent culture medium for preimplantation aneuploidy screening. Case presentation This case report elucidates the potential use of non-invasive preimplantation genetic testing for aneuploidy (PGT-A) as a valuable resource for couples facing infertility challenges. By using PGT-A, these couples can assess the genetic health of embryos before implantation, thereby increasing the chances of a successful pregnancy through assisted reproductive technologies. Conclusions PGT-A, an innovative technique using embryonic cell-free DNA isolated from a spent culture medium, offers a non-invasive and effective method for assessing chromosomal aberrations in embryos. It has the potential to enhance preimplantation genetic testing and support medically personalized embryo selection.